Evaluación de la viabilidad de instalación de un SSFV en las instalaciones del eco campus de la Universidad de América (2023)
The objective of this degree work is to evaluate the feasibility of installing a solar photovoltaic system (SSFV) in the facilities of the Eco Campus of the University of America. The SSFV is proposed as a sustainable solution for the generation of renewable energy and the reduction of the university's carbon footprint. Initially, the geographic location of the Eco Campus is evaluated to determine the amount of solar radiation available. This is achieved by analyzing climate data and considering factors such as latitude, altitude, and local weather conditions. The surface available for the installation of solar panels is examined, this includes identifying suitable areas, such as roofs of buildings, parking lots or open land, where the solar panels can be located, and then taking said data to simulation software. (PVsyst) and obtain very precise data on energy generation, coefficient of performance (PR), and net efficiency of the system.